The impact of grandchild care on depressive symptoms of grandparents in China: The mediating effects of generational support from children - Hong, Yue; Xu, Wei; Zhao, Lijuan (Frontiers in Public Health, 2023)
Objectives: Despite extensive studies about the direct effect of grandchild care on caregiver depression in China, understanding of its internal influencing mechanism has been limited. After controlling for socioeconomic factors, this study investigated whether the experience of caring for grandchildren had a long-term impact on the depression levels of grandparents, either directly or indirectly through generational support from adult children. Method: The subjects of this study were a total of 9,219 adults over 45 who participated in the China Health and Retirement Longitudinal Surveys in 2015 and 2018. We adopted a lag-behind variable to examine the impact of grandchild care on depressive symptoms of grandparents. The proposed mediation model was analyzed using bootstrap modeling, and the KHB method was conducted further to examine differences in the effects of generational support. Results: The experience of caring for grandchildren had a significant negative correlation with the depression level of Chinese grandparents. Moreover, children's support significantly mediated the impact of parenting experience on grandparents' depression. Significantly, instrumental support mediated the effect to the greatest extent, while emotional support from children contributed the least. The intermediary effect has urban‒rural heterogeneity. Conclusion: These findings indicated that grandchild care significantly inhibited the depression level of Chinese grandparents through increased intergenerational support from adult children. The implications of the study’s findings were discussed.